Implementation of Gender Equality Policy at Village Community Empowerment Office, Population Control, Family Planning, Women's Empowerment and Child Protection (PMDPPKBPPPA) in Barru Regency - Fadilah, Fadilah; Usman, Jaelan; Burhanuddin, Burhanuddin; Mappasere, Fatmawati A. (Jurnal Manajemen Pelayanan Publik, 2024)
Gender inequality has long been a national issue whose handling requires awareness from various parties so that the government issued a gender equality policy contained in the Sustainable Development Goals (SDGs) program with the policy of Law Number 1 of 2017 concerning Gender Mainstreaming. With these problems, researchers will analyze the implementation of gender equality policies at the PMDPPKBPPPA Office of Barru Regency so that gender injustice can be minimized. The method used is a qualitative approach with a case study research type. The results showed that the implementation of gender equality policies has been well implemented supported by George Edward III's theory with indicators of Communication, Resources, Disposition and Bureaucratic Structure. Communication of policy implementers is well established, adequate resource readiness, highly dedicated disposition of implementers and non-overlapping bureaucratic structures. So it can be concluded that the implementation of gender equality policies at the PMDPPKBPPPA Office of Barru Regency has been well implemented even though there are still indicators that need to be improved by policy implementers located on communication indicators where socialization is not optimal.